CEP55 promoted the migration, invasion and neuroshpere formation of the glioma cell line U251. (13th July 2019) - Li, Feng; Jin, Dan; Guan, Li; Zhang, Cheng-Chen; Wu, Ting; Wang, Yu-Jue; Gao, Dian-Shuai
Highlights: Centrosomal protein of 55 kDa (CEP55) was identified as a biomarker for multiple cancers. Overexpression of CEP55 promoted the invasion and migration of U251 cell. Overexpression of CEP55 promoted stem like cells' self-renewal. Overexpression of CEP55 enhanced the expression of Forkhead box protein M1 (FOXM1). Overexpression of CEP55 enhanced the expression of Matrix metalloproteinases (MMPs) and NF-κB pathway. Abstract: Glioma stem cells (GSC) were important for Glioblastoma (GBM) initiation and chemotherapy resistance. Centrosomal protein of 55 kDa (CEP55) was a biomarker for multiple cancers. However, roles and mechanism of CEP55 in glioma tumorigenesis and stemness maintains of stem like cells was still unclear. U251 cells which stable overexpression or downregulation of CEP55 was obtained by lentivirus mediated transduction. Roles and mechanism of CEP55 in stemness maintains of stem like cells and tumorigenesis was investigated. Our results implied that knockdown the expression of CEP55 inhibited the invasion and migration of U251 cells, while overexpression of CEP55 displayed opposite results. Moreover, overexpression of CEP55 promoted neurosphere formation of glioma stem-like cells, while CEP55 knockdown decreased the number and size of neurosphere. Mechanistically, overexpression of CEP55 enhanced the expression of Forkhead box protein M1 (FOXM1), Matrix metalloproteinases (MMPs) and activated the NF-κB pathway, while knockdown CEP55 displayed opposite results. In conclusion, our results indicated that CEP55 played an important role in promoting the invasion and migration of U251 cell and self-renewal of glioma stem like cells which might be a new therapeutic target for glioma.